Black hole image encoding quantum gravity information - Zhang, Cong; Ma, Yongge; Yang, Jinsong (Physical Review D, 2023)
The quantum extension of the Kruskal spacetime indicates the potential existence of a companion black hole in the universe earlier than ours. It is shown that the radiation from the companion black hole can enter its horizon, pass through the deep Planck region, and show up from the white hole in our Universe. These radiation inlay extra bright rings in the image of the black hole in our Universe, and some of these rings appear distinctly in the shadow region. Therefore, the image of the black hole observed by us encodes the information of quantum gravity. The positions and widths of the bright rings are predicted precisely. The predictive values for massive black holes are universal for a quite general class of quantum modified spacetime with the scenario of black hole to white hole transition. Thus, our result opens a new experimental window to test this prediction of quantum gravity.
CRIS-Team Scopus Importer:2024-12-16